Association between vitamin D receptor polymorphisms, tight junction proteins and clinical features of adult patients with atopic dermatitis - Teresa Grieco; Elisa Moliterni; Giovanni Paolino; Camilla Chello; Alvise Sernicola; Colin Gerard Egan; Fabrizio Nannipieri; Santina Battaglia; Marina Accoto; Erika Tirotta; Silvia Trasciatti; Silvano Bonaretti; et al. (Mattioli1885, 2024)
Background: Few studies have explored the intricate connections between vitamin D receptor (VDR) gene polymorphisms, VDR, tight junction (TJ) protein expression and clinical features of atopic dermatitis (AD). Methods: From 43 adult AD patients, VDR polymorphisms were genotyped from peripheral blood samples using polymerase chain reaction-restriction fragment length polymorphism. VDR, occludin, claudin-1 and ZO-1 protein expression from skin lesion biopsies were assessed by immunohistochemistry. Results: The A1012G heterozygous VDR polymorphism exhibited a lower odds ratio (OR) for juvenile AD onset (OR: 0.046, 95% CI 0.004-0.51, p=0.012). In contrast, the presence of ≥2 homozygous VDR polymorphisms were significantly associated with positive skin prick test (SPT) (10/20, 50%) vs. negative SPT (1/23, 4.3%; p=0.0003). The most highly expressed TJ proteins in lesions of AD patients were claudin-1 and ZO-1, while VDR and occludin were less prevalent. A significant correlation was observed between ZO-1 expression and a body mass index ≥30 kg/m2 (OR: 12.1, 95% CI 1.06-137.9, p=0.045). Claudin-1 expression was associated with a positive SPT (OR: 8.23, 95% CI 1.04-65.5, p=0.046) and serum 25(OH)D levels were negatively correlated with ZO-1 expression (rho= -0.43, p=0.0058). Conclusion: This study provides novel insights into the relationship between VDR gene polymorphisms, VDR, TJ protein expression, and clinical features in adult AD patients, highlighting a significant role of vitamin D in the pathophysiology of this disease.